Incidental findings on non-contrast abdominal computed tomography in an asymptomatic population: Prevalence, economic and health implications. - Alexander Ritter; Maximilian Sabev; Olivier Bonny; Gregoire Wuerzner; Thomas Ernandez; Florian Buchkremer; Stephan Segerer; Daniel G Fuster; Beat Roth; Nilufar Mohebbi; Lena Jellestad; Andreas M Hoetker; et al. (PLoS ONE)
Introduction Increasing use of low-dose abdominal computed tomography (CT) scans in clinical diagnostics and research offers high sensitivity for kidney stones with minimal radiation exposure. However, due to reduced specificity, incidental findings potentially lead to unnecessary follow-up, financial burden, and psychological distress. Gaps of knowledge remain regarding the prevalence of incidental findings and their financial and psychological consequences. This study investigates the prevalence of incidental findings in asymptomatic participants undergoing low-dose non-contrast CT scans and their economic and psychological sequelae. Methods We conducted a retrospective, multicentric observational study using data from the assessment for the control group of the Swiss Kidney Stone Cohort (SKSC). Low-dose non-contrast CT scans were analyzed for incidental findings, cost and psychological impact. Statistical analyses evaluated participant characteristics, financial and psychological consequences. Results 229 participants underwent low-dose non-contrast CT scans, with 112 correctly completing the psychological questionnaires. The mean age was 42.9 years, and 56.3% were male. Incidental findings were observed in 47.2% (n = 108) of participants, with 16.6% having multiple findings. Kidney-related findings were the most prevalent, accounting for 35% of all findings. Of the incidental findings, 37.9% were classified as "incidentalomas" by the American College of Radiology (ACR) guidelines, and 15.7% of participants had findings that warranted follow-up according to radiology reports. In terms of costs, follow-up procedures, including imaging, consultations, and surgeries, incurred a total expense of 44'988 CHF, averaging 1967 CHF per participant and 2'999 CHF per incidental finding requiring follow-up. Surgical interventions were necessary for three participants, with individual costs reaching up to 35'208 CHF. Psychological assessment revealed that emotional distress and level of concern significantly differed across resilience levels and categories of CT findings. Participants with high resilience demonstrated lower emotional distress and concern, while those with CT findings requiring follow-up exhibited higher distress. Emotional distress was significantly greater in participants with follow-up findings compared to those without. Conclusions Low-dose non-contrast abdominal CT scans often reveal incidental findings. Follow-up tests and procedures incurred significant financial costs, occasionally even leading to unnecessary surgical or non-surgical interventions. Psychological assessments showed increased anxiety in participants requiring follow-up, particularly those with low resilience. Our findings highlight the need for improved management, patient information, and consideration of economic and psychological impacts of incidental findings in clinical research and routine in the future.